Does parental phubbing aggravates adolescent sleep quality problems? - Qian Ding; Qian Ding; Siwei Dong; Yongxin Zhang (Frontiers in Psychology, 2023)
ObjectiveBased on the theoretical model for the “stress–sleep” relationship, this study investigated the impact of parental phubbing on adolescent sleep quality problems and a moderated mediation mechanism.MethodsA total of 781 adolescents was surveyed using the Chinese version of Parental Phubbing Scale, the Ultra-brief Screening Scale for Depression and Anxiety Scale, the Self-Control Questionnaire for Chinese children, and the Chinese version of Pittsburgh Sleep Quality Index Scale.ResultsParental phubbing and negative emotions were significantly and positively correlated to sleep quality problems, but self-control was not correlated to sleep quality problems. Parental phubbing directly influenced sleep quality problems and also indirectly influenced sleep quality problems through the mediating effect of negative emotions. Moreover, self-control played a moderating role in the path of parental phubbing affecting negative emotions. That is, the effect was more significant for adolescents low in self-control relative to those high in self-control.ConclusionParental phubbing is a risk factor for adolescent sleep quality problems. This study is the first to demonstrate empirical evidence for the relationship between parental phubbing and sleep quality problems.